2020
DOI: 10.2217/epi-2020-0154
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SARS-CoV-2 Using Polycomb Inhibitors as Antiviral Agents

Abstract: Mechanistically, these viruses activate several epigenetic effectors, including the polycomb repressive complex 2 (PRC2), which mediates H3K27me3 at the promoter of certain IFN-stimulated genes repressing transcription. "

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…It was reported that pathogenic influenza viruses and coronaviruses control IFN‐stimulated gene responses by polycomb repressive complex 2‐mediated H3K27me3 at the promoter region of certain IFN‐stimulated genes (Menachery et al, 2014). It is not yet known whether SARS‐CoV‐2 uses the same epigenetic mechanisms, but potential epigenetically regulated factors have been reported, and it would be worth exploring these to find out successful treatment strategies as hypothesized by Ayaz and Crea (2020).…”
Section: Epigenetic Factorsmentioning
confidence: 99%
“…It was reported that pathogenic influenza viruses and coronaviruses control IFN‐stimulated gene responses by polycomb repressive complex 2‐mediated H3K27me3 at the promoter region of certain IFN‐stimulated genes (Menachery et al, 2014). It is not yet known whether SARS‐CoV‐2 uses the same epigenetic mechanisms, but potential epigenetically regulated factors have been reported, and it would be worth exploring these to find out successful treatment strategies as hypothesized by Ayaz and Crea (2020).…”
Section: Epigenetic Factorsmentioning
confidence: 99%
“…Interestingly, the polycomb repressive complex 2 (PRC2), which mediates transcription repression via H3K27me3 enrichment at specific IFN-stimulated genes, could also be considered a target. Pharmacologic inhibitors of PRC2 are currently in advanced clinical trials for cancer treatment and could be easily repurposed to treat COVID-19 patients [ 91 ].…”
Section: Epigenetic Implication In Sars- Cov-2 Infection and Therapymentioning
confidence: 99%
“… 123 Interestingly, influenza A viruses, MERS-CoV, and SARS-CoV are able to activate the PRC2, which, in turn, increases the levels of H3K27me3 (repressive mark) at the promoters of targeted IFN-stimulated genes to counteract the host antiviral immune response. 124 This let us suggest that also SARS-CoV-2 might use the same mechanisms to inactive IFN-related pathways in infected cells; besides, since polycomb inhibitors have shown a general antiviral activity, 125 it might be useful to investigate whether hydroxychloroquine can directly impact on PRC2 activity in COVID-19.…”
Section: Epidrug Repurposingmentioning
confidence: 99%